The healthy participant effect: insights and results from a population-based case-control study on breast cancer - Maldonado-Cañón, Kevin; Möhl, Annika; Obi, Nadia; Behrens, Sabine; Flaßkamp, Fabian; Seibold, Petra Beate; Chang-Claude, Jenny; Becher, Heiko (American journal of epidemiology, 2025)
Agreement to participate in case-control studies has become low. Healthy participant bias resulting from differential response proportions in cases and controls can distort results; however, the magnitude of bias is difficult to assess. We investigated the effect in a large population-based case-control study on breast cancer, with a participation rate of 43.4% and 64.1% for controls and cases, respectively. We performed a mortality follow-up in 2020 for 3813 cases and 7335 controls recruited during 2002-2005. Standardized mortality ratios (SMRs) for overall mortality and selected causes of death were estimated. The mean age at recruitment was 63.1 years. The overall mortality for controls was 0.66 times lower (95% CI, 0.62-0.69) than for the reference population. For causes of death other than breast cancer, SMRs were similar in cases and controls (0.70 and 0.64). Higher education was associated with lower SMRs in both cases and controls. Options for adjusting the healthy participant bias are limited if the true risk factor distribution in the underlying population is unknown. However, a relevant bias in this particular case-control study is considered unlikely since a similar healthy participant effect was observed for both controls and cases.